DEWAX Transcription Factor Is Involved in Resistance to Botrytis cinerea in Arabidopsis thaliana and Camelina sativa - Ju, Seulgi; Go, Young Sam; Choi, Hyo Ju; Park, Jeong Mee; Suh, Mi Chung (Frontiers in Plant Science, 2017)
The cuticle of land plants is the first physical barrier to protect their aerial parts from biotic and abiotic stresses. DEWAX, an AP2/ERF-type transcription factor, negatively regulates cuticular wax biosynthesis. In this study, we investigated the resistance to Botrytis cinerea in Arabidopsis thaliana and Camelina sativa overexpressing DEWAX and in Arabidopsis dewax mutant. Compared to wild type (WT) leaves, Arabidopsis DEWAX OX and dewax leaves were more and less permeable to toluidine blue dye, respectively. The ROS levels increased in DEWAX OX leaves, but decreased in dewax relative to WT leaves. Compared to WT, DEWAX OX was more resistant, while dewax was more sensitive to B. cinerea; however, defense responses to Pseudomonas syringae pv. tomato DC3000:GFP were inversely modulated. Microarray and RT-PCR analyses indicated that the expression of defense-related genes was upregulated in DEWAX OX, but downregulated in dewax relative to WT. Transactivation assay showed that DEWAX upregulated the expression of PDF1.2a, IGMT1, and PRX37. ChIP assay revealed that DEWAX directly interacts with the GCC-box motifs of PDF1.2a promoter. In addition, ectopic expression of DEWAX increased the tolerance to B. cinerea in C. sativa. Taken together, we suggest that increased ROS accumulation and DEWAX-mediated upregulation of defense-related genes are closely associated with enhanced resistance to B. cinerea in Arabidopsis and C. sativa.